Preparation method of methane cracking hydrogen production and carbon nanotube catalyst

Preparation of alumina-supported iron-nickel catalysts through one-step synthesis and inert gas calcination method, solving the problem of difficult control of catalyst size and composition in the prior art, achieving nano-level catalyst preparation and efficient methane cracking performance, suitable for large-scale applications .

CN119140099APending Publication Date: 2024-12-17苏州福睿能源有限责任公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411332843.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the preparation method for alumina-supported iron-nickel catalyst is complex and difficult to control the size, composition and morphology of the catalyst, which limits its large-scale application.

Method used

The iron-nickel alloy nanoparticles supported by hydrated alumina precursors were synthesized by a one-step method, and the iron-nickel catalyst supported by alumina was calcined under an inert gas atmosphere, achieving controllable particle size and high dispersion at the nanoscale.

Benefits of technology

This method simplifies the process flow, realizes the composition of the catalyst uniform and adjustable, and shows good catalytic performance of high-temperature methane cracking, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of catalyst preparation methods, in particular to a preparation method of a carbon nanotube catalyst for hydrogen production through methane cracking. The method comprises the following steps: S1, synthesizing hydrated alumina precursor loaded iron-nickel alloy nanoparticles by adopting a one-step method; and S2, in an inert gas atmosphere, roasting the iron-nickel alloy nanoparticles to prepare the aluminum oxide loaded iron-nickel alloy nanoparticle catalyst. According to the invention, hydrated alumina precursor-loaded iron-nickel alloy nanoparticles are synthesized by a one-step method, and then are roasted in an inert gas atmosphere to prepare the alumina-loaded iron-nickel catalyst. The catalyst prepared by the method can reach a nanometer level, is controllable in particle size, high in dispersity and uniform and adjustable in composition, and shows good catalytic performance on high-temperature methane cracking reaction. Compared with the prior art, the method is simple in process and can be used for large-scale synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalyst preparation methods, in particular to methods for preparing methane cracking hydrogen production and carbon nanotube catalysts. Background Art

[0002] The main component of natural gas is methane, which can produce high value-added hydrogen and carbon nanotubes through high-temperature cracking. At the same time, there is no greenhouse gas emission in the product, the atomic conversion rate is high, and the cost is low. After the high-temperature cracking reaction of methane, the high-purity hydrogen produced can be directly used in proton exchange membrane fuel cells without further purification. The obtained carbon nanotube products have high economic value. Due to their special structure and morphology, excellent mechanical, electrical, heat transfer and other properties, they have very broad market prospects in the field of fuel cells or advanced functional materials. Methane cracking to produce hydrogen and carbon nanotubes not only meets the environmental protection requirements of our modern society, but has also become a hot topic in industrial applications, especially in the field of new energy.

[0003] Methane is a highly stable molecule. In the absence of a catalyst, carbon and hydrogen can only be broken down and reacted at 1200°C; in the presence of a catalyst, the reaction can be carried out at 300-800°C. The most commonly used catalyst for methane catalytic cracking is a supported catalyst: the active components in the catalyst include transition metals (Fe, Ni and Co) and precious metals (Pd, Pt and Ir), and the catalyst carriers include Al2O3, SiO2, TiO2, CeO2 and Ln2O3. Among them, alumina-supported iron-nickel catalysts have attracted much attention due to their high catalytic activity and stability, as well as low cost. Commonly used methods for preparing alumina-supported iron-nickel catalysts include impregnation, precipitation and sol-gel methods. The above methods are relatively cumbersome and complex, and the size, composition and morphology of the catalyst are difficult to control, which limits the large-scale application of such catalysis. Summary of the invention

[0004] The technical problem to be solved by the present invention is: In order to solve the technical problem described in the background technology, the present invention provides a method for preparing a catalyst for hydrogen production by cracking methane and carbon nanotubes. The present application adopts a one-step method to synthesize iron-nickel alloy nanoparticles supported by a hydrated alumina precursor, and then calcines them under an inert gas atmosphere to prepare an alumina-supported iron-nickel catalyst. The catalyst prepared by this method can reach the nanometer level, with controllable particle size and high dispersion, uniform and adjustable composition, and exhibits good catalytic performance for high-temperature methane cracking reactions. Compared with the prior art, this method has a simple process and can be synthesized on a large scale.

[0005] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a methane cracking hydrogen production and carbon nanotube catalyst comprises the following steps: S1, synthesizing Fe-Ni alloy nanoparticles supported by hydrated alumina precursor using a one-step method; S2. In an inert gas atmosphere, the iron-nickel alloy nanoparticles are calcined to prepare an alumina-supported iron-nickel alloy nanoparticle catalyst.

[0006] Specifically, in step S1, the method for preparing the iron-nickel alloy nanoparticles is: S11, adding aluminum nitrate, iron nitrate and nickel nitrate into water and stirring evenly to form a mixed solution; S12, adding concentrated ammonia water to the mixed solution to form a mixed suspension, and letting it stand for a period of time; S13, adding sodium borohydride solution to the mixed suspension, performing ultrasonic reaction at room temperature, and then centrifuging to obtain a mixed precipitate; S14. Dry the mixed precipitate to obtain iron-nickel alloy nanoparticles supported by a hydrated alumina precursor.

[0007] Specifically, the iron-nickel alloy nanoparticles supported by the hydrated alumina precursor are placed in a muffle furnace and treated in a nitrogen atmosphere to obtain an alumina-supported iron-nickel alloy nanoparticle catalyst.

[0008] Specifically, in step S11, the mixed solution is a nitrate solution, and the nitrate solution contains Ni 2+ , Fe 3+ 、Al 3+ ; (Ni 2+ +Fe 3+ ):Al 3+ The molar ratio is 1:1 to 1:10; Ni 2+ : Fe 3+ The molar ratio is 1:3 to 3:1; the total concentration of the nitrate solution is 10% to 30%.

[0009] Specifically, in step S12, the pH of the mixed suspension is 8-10.

[0010] Specifically, the concentration of the sodium borohydride solution is 0.1 to 1 mol / L; the sodium borohydride solution contains Ni 2+ , Fe 3+ , NaBH4; (Ni 2+ +Fe 3+ ):NaBH4 molar ratio is 1:5~1:10.

[0011] Specifically, in step S14, the temperature of the mixed precipitate in the oven is increased at a rate of 10° C. / min.

[0012] Specifically, in step S12, the mixed suspension is allowed to stand for 2-6 hours; In step S13, the ultrasonic reaction time is 2 to 4 hours; In step S14, the mixed precipitate is dried in an oven for 24 to 72 hours at a drying temperature of 100 to 120°C.

[0013] Specifically, the treatment temperature of the iron-nickel alloy nanoparticles in the muffle furnace is 400-500° C., and the treatment time is 6-24 hours.

[0014] Specifically, the nitrogen flow rate is 2-5 m / s, and the heating rate is 10° C. / min.

[0015] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a catalyst for hydrogen production by cracking methane and a carbon nanotube. The present application adopts a one-step method to synthesize iron-nickel alloy nanoparticles supported by a hydrated alumina precursor, and then calcines them in an inert gas atmosphere to prepare an iron-nickel catalyst supported by alumina. The catalyst prepared by the method can reach the nanometer level, with controllable particle size and high dispersion, uniform and adjustable composition, and exhibits good catalytic performance for high-temperature methane cracking reactions. Compared with the prior art, the method is simple in process and can be synthesized on a large scale. DETAILED DESCRIPTION

[0016] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a methane cracking hydrogen production and carbon nanotube catalyst comprises the following steps: Step 1: Add aluminum nitrate, iron nitrate and nickel nitrate into water and stir evenly to form a mixed solution; the mixed solution is a nitrate solution, and the nitrate solution contains Ni 2+ , Fe 3+ 、Al 3+ . 2+ +Fe 3+ ):Al 3+ The molar ratio is 1:1 to 1:10; Ni 2+ :Fe 3+ The molar ratio is 1:3 to 3:1; the total concentration of the nitrate solution is 10% to 30%.

[0017] Step 2: Add concentrated ammonia water to the mixed solution to form a mixed suspension, and let it stand for a period of time; the pH of the mixed suspension is 8-10. The standing time of the mixed suspension is 2-6 hours.

[0018] Step 3: Add sodium borohydride solution to the mixed suspension, perform ultrasonic reaction at room temperature, and the ultrasonic reaction time is 2 to 4 hours; centrifuge to obtain a mixed precipitate; the concentration of the sodium borohydride solution is 0.1 to 1 mol / L; the sodium borohydride solution contains Ni 2+ , Fe 3+ , NaBH4; (Ni 2+ +Fe 3+ ):NaBH4 molar ratio is 1:5~1:10.

[0019] Step 4: Dry the mixed precipitate to obtain iron-nickel alloy nanoparticles supported by a hydrated alumina precursor. The mixed precipitate is dried in an oven for 24 to 72 hours at a drying temperature of 100 to 120° C. The heating rate of the mixed precipitate in the oven is 10° C. / min.

[0020] Step 5: The iron-nickel alloy nanoparticles supported by the hydrated alumina precursor are placed in a muffle furnace and treated in a nitrogen atmosphere to obtain an alumina-supported iron-nickel alloy nanoparticle catalyst. The treatment temperature of the iron-nickel alloy nanoparticles in the muffle furnace is 400-500°C, and the treatment time is 6-24h. The nitrogen flow rate is 2-5m / s, and the heating rate is 10°C / min. Example 1

[0021] Molar ratio (Ni 2+ +Fe 3+ ):Al 3+ =1:9,Ni 2+ :Fe 3+ = 1:1, the total concentration of the nitrate solution is 10%, 0.39g of nickel nitrate, 0.54g of iron nitrate, and 9.07g of aluminum nitrate are weighed separately and dissolved in 100mL of deionized water, and stirred for 10min to completely dissolve the nitrate to form a mixed solution.

[0022] Add 25% concentrated ammonia water to the mixed solution to form a mixed suspension, adjust the pH of the mixed suspension to 10, and let it stand for 4 hours.

[0023] According to the concentration of sodium borohydride solution of 0.15 mol / L, (Ni 2+ +Fe 3+ ):NaBH4 molar ratio is 1:5, weigh 0.51g of sodium borohydride and dissolve it in 10mL of deionized water. Add the newly prepared sodium borohydride solution to the mixed suspension, react with ultrasound for 2h at room temperature, and obtain a mixed precipitate after centrifugation.

[0024] The oven temperature was set at 100°C, the heating rate was 10°C / min, and the mixed precipitate was dried for 24 h.

[0025] The flow rate of nitrogen was 25 m / s, the heating rate was 10°C / min, the temperature of the muffle furnace was 400°C, and the dried mixed precipitate was placed in the muffle furnace. In a nitrogen atmosphere, the mixture was treated at 400°C for 24 hours to obtain an alumina-supported iron-nickel alloy nanoparticle catalyst. Example 2

[0026] Molar ratio (Ni 2+ +Fe 3+ ):Al 3+ =1:9,Ni 2+ :Fe 3+ = 2:1, the total concentration of the nitrate solution is 10%, 0.55g of nickel nitrate, 0.38g of iron nitrate, and 9.07g of aluminum nitrate are weighed separately and dissolved in 100mL of deionized water, and stirred for 10min to completely dissolve the nitrate to form a mixed solution.

[0027] Add 25% concentrated ammonia water dropwise into the mixed solution to form a mixed suspension, adjust the pH of the mixed suspension to 10, and let it stand for 4 hours.

[0028] According to the concentration of sodium borohydride solution of 0.15 mol / L, (Ni 2+ +Fe 3+ ):NaBH4 molar ratio is 1:5, weigh 0.51g of sodium borohydride and dissolve it in 10mL of deionized water. Add the newly prepared sodium borohydride solution to the mixed suspension, react with ultrasound for 2h at room temperature, and obtain a mixed precipitate after centrifugation.

[0029] The oven temperature was set at 100°C, the heating rate was 10°C / min, and the mixed precipitate was dried for 24 h.

[0030] The flow rate of nitrogen was 25 m / s, the heating rate was 10°C / min, the temperature of the muffle furnace was 400°C, and the dried mixed precipitate was placed in the muffle furnace. In a nitrogen atmosphere, the mixture was treated at 400°C for 24 hours to obtain an alumina-supported iron-nickel alloy nanoparticle catalyst. Example 3

[0031] Molar ratio (Ni 2+ +Fe 3+ ):Al 3+ =1:9,Ni 2+ :Fe 3+ = 3:1, the total concentration of the nitrate solution is 10%, 0.64g of nickel nitrate, 0.29g of iron nitrate, and 9.07g of aluminum nitrate are weighed separately and dissolved in 100mL of deionized water, and stirred for 10min to completely dissolve the nitrate to form a mixed solution.

[0032] Add 25% concentrated ammonia water dropwise into the mixed solution to form a mixed suspension, adjust the solution pH to 10, and let stand for 4 hours.

[0033] According to the concentration of sodium borohydride solution of 0.15 mol / L, (Ni 2+ +Fe 3+):NaBH4 molar ratio is 1:5, weigh 0.51g of sodium borohydride and dissolve it in 10mL of deionized water. Add the newly prepared sodium borohydride solution to the mixed suspension, react with ultrasound for 2h at room temperature, and obtain a mixed precipitate after centrifugation.

[0034] The oven temperature was set at 100°C, the heating rate was 10°C / min, and the mixed precipitate was dried for 24 h.

[0035] The flow rate of nitrogen was 25 m / s, the heating rate was 10°C / min, the temperature of the muffle furnace was 400°C, and the dried mixed precipitate was placed in the muffle furnace. In a nitrogen atmosphere, the mixture was treated at 400°C for 24 hours to obtain an alumina-supported iron-nickel alloy nanoparticle catalyst.

[0036] Performance Testing Example 1 Example 2 Example 3 Catalyst specific surface area <![CDATA[11.0 m 2 / g]]> <![CDATA[9.6 m 2 / g]]> <![CDATA[8.5 m 2 / g]]> Methane conversion rate 65% 58% 42% Carbon nanotube diameter ~30nm ~20nm ~20nm In summary, compared with the prior art, the present invention is simple and easy to operate. The iron-nickel catalyst prepared by the method can reach the nanometer level, has controllable particle size, high dispersion, uniform and adjustable composition, and can be synthesized on a large scale. It exhibits good catalytic performance for high-temperature methane cracking reaction, and can obtain carbon nanotubes with uniform particle size.

[0037] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a methane cracking hydrogen production and carbon nanotube catalyst, characterized in that: The following steps are involved: S1, synthesizing Fe-Ni alloy nanoparticles supported by hydrated alumina precursor using a one-step method; S2. In an inert gas atmosphere, the iron-nickel alloy nanoparticles are calcined to prepare an alumina-supported iron-nickel alloy nanoparticle catalyst.

2. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 1, characterized in that: In step S1, the method for preparing the iron-nickel alloy nanoparticles is: S11, adding aluminum nitrate, iron nitrate and nickel nitrate into water and stirring evenly to form a mixed solution; S12, adding concentrated ammonia water to the mixed solution to form a mixed suspension, and letting it stand for a period of time; S13, adding sodium borohydride solution to the mixed suspension, performing ultrasonic reaction at room temperature, and then centrifuging to obtain a mixed precipitate; S14. Dry the mixed precipitate to obtain iron-nickel alloy nanoparticles supported by a hydrated alumina precursor.

3. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 2, characterized in that: The iron-nickel alloy nanoparticles supported by the hydrated alumina precursor are placed in a muffle furnace and treated in a nitrogen atmosphere to obtain an alumina-supported iron-nickel alloy nanoparticle catalyst.

4. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 1, characterized in that: In step S11, the mixed solution is a nitrate solution, and the nitrate solution contains Ni 2+ , Fe 3+ 、Al 3+ ; (Ni 2+ +Fe 3+ ):Al 3+ The molar ratio is 1:1 to 1:10; Ni 2+ : Fe 3+ The molar ratio is 1:3 to 3:1; the total concentration of the nitrate solution is 10% to 30%.

5. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 1, characterized in that: In step S12, the pH of the mixed suspension is 8-10.

6. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 1, characterized in that: The concentration of the sodium borohydride solution is 0.1 to 1 mol / L; the sodium borohydride solution contains Ni 2+ , Fe 3+ , NaBH4; (Ni 2+ +Fe 3+ ):NaBH4 molar ratio is 1:5~1:

10.

7. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 1, characterized in that: In the step S14, the temperature of the mixed precipitate in the oven is increased at a rate of 10°C / min.

8. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 2, characterized in that: In step S12, the mixed suspension is allowed to stand for 2-6 hours; In step S13, the ultrasonic reaction time is 2 to 4 hours; In step S14, the mixed precipitate is dried in an oven for 24 to 72 hours at a drying temperature of 100 to 120°C.

9. The method for preparing a methane cracking hydrogen production and carbon nanotube catalyst according to claim 3, characterized in that: The processing temperature of the iron-nickel alloy nanoparticles in the muffle furnace is 400-500° C., and the processing time is 6-24 hours.

10. The method for preparing methane cracking hydrogen and carbon nanotube catalyst according to claim 3, characterized in that: The nitrogen flow rate is 2-5 m / s, and the heating rate is 10° C. / min.

Citation Information

Patent Citations

  • Methane cracking catalyst and preparation method thereof

    CN111185179A

  • Nickel oxide nanoparticles as catalyst precursor for hydrogen production

    US20060198782A1

  • Methane steam reforming, using nickel / alumina nanocomposite catalyst or nickel / silica-alumina hybrid nanocomposite catalyst

    US20170001863A1